Association Between Running Shoe Characteristics and Lower Extremity Injuries in United States Military Academy Cadets. Issue 12 (October 2019) - Helton, Gary L.; Cameron, Kenneth L.; Zifchock, Rebecca A.; Miller, Erin; Goss, Donald L.; Song, Jinsup; Neary, Michael T.
Background: Running-related overuse injuries are very common among recreational runners, with the reported annual injury rates ranging from 39% to 85%. Relatively few large prospective cohort studies have been conducted to investigate injury risk associated with different running shoe characteristics, and the results of the existing studies are often contradictory. Purpose/Hypothesis: The purpose was to investigate the relationship between running shoe characteristics and lower extremity musculoskeletal injury. It was hypothesized that the risk of injury would be increased in individuals wearing shoes with minimal torsional stiffness and heel height compared with those wearing shoes with greater levels of torsional stiffness and heel height. Study Design: Cohort study; Level of evidence, 2. Methods: The study included 1025 incoming cadets. Shoe torsional stiffness and heel height were calculated and recorded. Demographic data were recorded and analyzed as potential covariates. Lower extremity injuries sustained over 9 weeks during cadet basic training were documented by use of the Armed Forces Health Longitudinal Technology Application and the Cadet Illness and Injury Tracking System. Kaplan-Meier survival curves were estimated, with time to incident lower extremity injury as the primary outcome by level of the independent predictor variables. Risk factors or potential covariates were carried forward into multivariable Cox proportional hazards regression models. Absolute and relative risk reduction and numbers needed to treat were calculated. Results: Approximately 18.1% of participants incurred a lower extremity injury. Cadets wearing shoes with moderate lateral torsional stiffness were 49% less likely to incur any type of lower extremity injury and 52% less likely to incur an overuse lower extremity injury than cadets wearing shoes with minimal lateral torsional stiffness, both of which were statistically significant observations. Injury risk was similar among cadets wearing shoes with minimal and extreme lateral torsional stiffness. Conclusion: Shoes with mild to moderate lateral torsional stiffness may be appropriate in reducing risk of lower extremity injury in cadets. Shoes with minimal lateral torsional stiffness should be discouraged in this population.